2022
DOI: 10.1007/s11060-022-03969-x
|View full text |Cite
|
Sign up to set email alerts
|

Same-day discharge after brain tumor resection: a prospective pilot study

Abstract: Purpose Outpatient brain surgery has many advantages for the psychological and physical wellbeing of patients, as well as reduced costs to the health care system. Compared with inpatient admissions, same day discharges reduce patient exposure to nosocomial infection, thromboembolic complications, and medical error. We aim to establish a prospectively collected quality outcomes database to examine the outcomes of patients that undergo brain tumor resection and are discharged home the same day as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…As health care costs increase in developed nations, particularly in the US, there is an increasing focus on strategies that maintain or improve patient outcomes while being economically efficient . In neurosurgery, and brain tumor surgery in particular, multiple centers have reported their experience decreasing mean LOS and achieving same-day discharge . But progress to reduce mean LOS for awake craniotomy lags behind other surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As health care costs increase in developed nations, particularly in the US, there is an increasing focus on strategies that maintain or improve patient outcomes while being economically efficient . In neurosurgery, and brain tumor surgery in particular, multiple centers have reported their experience decreasing mean LOS and achieving same-day discharge . But progress to reduce mean LOS for awake craniotomy lags behind other surgical specialties.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding short-term risk of deterioration after same-day discharge have prevented a wider adoption of standards and practices aimed at same-day craniotomies and faster discharge times. Regardless, multiple centers have attempted to change their practices to enable same-day discharge . Recently, Vallejo et al reported on the implementation of an outpatient craniotomy program applicable to 37 of 334 patients undergoing craniotomy, with successful same-day discharge in 32 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Definitive guidelines are still lacking regarding patient selection criteria and perioperative protocol. We suggest a perioperative care pathway protocol for SDNS, adapted from multiple studies (Tables 1 and 2) [2–4,13,16,18 ▪▪ ,19 ▪ ,20 ▪ ,21,22,23 ▪ ]. Advanced perioperative management strategies, such as optimization of comorbidities, preoperative medical clearance, and close monitoring during the peri-operative period, are crucial in mitigating the risks associated with comorbidities in SDNS.…”
Section: Perioperative Pathway: Fast-track Protocol For Same-day Neur...mentioning
confidence: 99%